2019
DOI: 10.15835/nbha47411610
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a SEPALLATA-like MADS-box Gene from Cucumber (Cucumis sativus L.)

Abstract: SEPALLATA (SEP) genes encode the E class MADS-box transcription factors that play vital roles in various aspects of plant growth and development. In this study, we isolated a SEP-like gene from cucumber (Cucumis sativus L.), which was previously named as CsMADS01. CsMADS01 had a coding sequence (CDS) of 741 bp, and coded a deduced protein of 246 amino acid residues that was predicted to be located in the nucleus. The putative CsMADS01 protein was typically characterized by the MIKC-type MADS (including MADS, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Among these genes, CsSAP1, CsSAP6, CsSAP7, and CsSAP11 displayed the highest transcriptional levels in unfertilized ovaries; CsSAP4, CsSAP5, CsSAP10, and CsSAP12 exhibited much higher transcript abundance in flowers; while CsSAP8 and CsSAP9 showed the highest mRNA accumulation in roots and basal tendrils, respectively (Figure 6A). To further explore the possible roles of CsSAP genes in fruit development, the transcript levels of CsSAP genes at different fruit development stages were evaluated according to the previously reported RNA-seq data [40]. The transcriptome data showed that several CsSAP genes, such as CsSAP1, CsSAP5, CsSAP7, CsSAP9, CsSAP11, and CsSAP12, displayed remarkable transcriptions at certain time points during fruit development (Figure 6B).…”
Section: Expression Profiles Of Cssap Genes In Different Tissues and During Fruit Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these genes, CsSAP1, CsSAP6, CsSAP7, and CsSAP11 displayed the highest transcriptional levels in unfertilized ovaries; CsSAP4, CsSAP5, CsSAP10, and CsSAP12 exhibited much higher transcript abundance in flowers; while CsSAP8 and CsSAP9 showed the highest mRNA accumulation in roots and basal tendrils, respectively (Figure 6A). To further explore the possible roles of CsSAP genes in fruit development, the transcript levels of CsSAP genes at different fruit development stages were evaluated according to the previously reported RNA-seq data [40]. The transcriptome data showed that several CsSAP genes, such as CsSAP1, CsSAP5, CsSAP7, CsSAP9, CsSAP11, and CsSAP12, displayed remarkable transcriptions at certain time points during fruit development (Figure 6B).…”
Section: Expression Profiles Of Cssap Genes In Different Tissues and During Fruit Developmentmentioning
confidence: 97%
“…The expression profile of CsSAP genes was examined based on the available RNA-seq data in different cucumber tissues and during fruit ripening [39,40]. As shown in Figure 6A, nearly all CsSAP genes were expressed in the tested tissues, except for CsSAP2 and CsSAP3.…”
Section: Expression Profiles Of Cssap Genes In Different Tissues and During Fruit Developmentmentioning
confidence: 99%
“…To our knowledge, very little is known about the expression and function of MADS-box TF genes in melon. Most studies have been carried out in cucumber, and all correlated the expression of these genes with different reproductive developmental functions and fruit maturation ( Cheng et al , 2019 , 2020 ). The transition of the melon inflorescence from meristematic status to floral organ differentiation is accompanied by the downregulation of meristem activity genes and a significant upregulation of a large number of genes associated with organ development.…”
Section: Discussionmentioning
confidence: 99%